EVALUASI PENDIDIKAN KARAKTER BERBASIS ISLAM: STRATEGI GURU PENDIDIKAN AGAMA ISLAM DALAM MENINGKATKAN KARAKTER RELIGIUS SISWA DI SEKOLAH MENENGAH PERTAMA NEGERI 07 MUARO JAMBI - Atiah Almubarokah; Hasanda Putra, Fio; Vindia Putri; Zawaqi Afdal Jamil (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the strategies implemented by Islamic Religious Education (PAI) teachers in enhancing students’ religious character at State Junior High School 7 Muaro Jambi. Religious character plays an important role in shaping students’ personalities based on Islamic values such as discipline, responsibility, and tolerance. The research method used is qualitative research with a descriptive approach. Data collection techniques were carried out through observation, interviews, and documentation. The research subjects consisted of the principal, Islamic Religious Education teachers, and students of class VIII A. The collected data were analyzed using the Miles and Huberman interactive model, which includes data reduction, data display, and conclusion drawing. The results of the study indicate that the strategies implemented by teachers in improving students’ religious character include habituation of religious activities such as congregational prayer, reading the Qur’an, praying before and after learning, as well as the application of exemplary methods and character development based on Islamic values. Supporting factors for the success of this strategy include support from the school, adequate worship facilities, and collaboration with parents. However, there are also several obstacles such as the lack of parental involvement and the less conducive influence of the external environment. This study emphasizes that the role of teachers is very important in shaping students’ religious character. Systematic strategies and support from various parties are needed to create a learning environment that strengthens students’ religious values.